2012
DOI: 10.1542/peds.2011-1218
|View full text |Cite
|
Sign up to set email alerts
|

Lead Poisoning in United States-Bound Refugee Children: Thailand-Burma Border, 2009

Abstract: The prevalence of elevated blood lead levels among tested US-bound Burmese refugee children was higher than the current US prevalence, and was especially high among children <2 years old. Refugee children may arrive in the United States with elevated blood lead levels. A population-specific understanding of preexisting lead exposures can enhance postarrival lead-poisoning prevention efforts, based on Centers for Disease Control and Prevention recommendations for resettled refugee children, and can lead to reme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…Moreover, we identified EBLLs in 30.6% of all children, an alarming rate considering the neurotoxic potential of Lead, its negative impact on cognitive function and attention span [21, 3941]. Due to accumulating evidence regarding the significant and irreversible adverse effects of even low levels of circulating blood Lead, the Centers for Disease Control and Prevention (CDC) decreased in 2012 the respective “reference level” to 5 μg/dL, stating however that no level of Lead is considered safe.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we identified EBLLs in 30.6% of all children, an alarming rate considering the neurotoxic potential of Lead, its negative impact on cognitive function and attention span [21, 3941]. Due to accumulating evidence regarding the significant and irreversible adverse effects of even low levels of circulating blood Lead, the Centers for Disease Control and Prevention (CDC) decreased in 2012 the respective “reference level” to 5 μg/dL, stating however that no level of Lead is considered safe.…”
Section: Discussionmentioning
confidence: 99%
“…25 Furthermore, several studies have shown an increase in acute and chronic malnutrition, including micronutrient and vitamin deficiencies in refugee camps in Jordan 26 and Nepal. 27 In addition, elevated levels of lead in toxic concentrations have been found in refugee camps in Thailand 28 and Somalia (►Fig. 2).…”
Section: Refugee Campsmentioning
confidence: 99%
“…The elevation was caused by premigration exposure to car batteries and contaminated traditional medicines. 11,12 This led to premigration interventions, as well as the US engaging the IRHWG to disseminate its data. At that time, one-third of Australia-bound refugees came from the Burma region 13 , so Australia capitalised on the shared data and action to minimise the risk of lead harm to refugees resettling here.…”
Section: Information Exchangementioning
confidence: 99%